(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses the issues of improving the methodology for developing special competencies of future teachers through digital technologies. The need to modernize pedagogical activities in the education system, improve the professional skills of teachers and adapt to the modern labor market in the conditions of digital transformation is analyzed. The article studies international experiences such as UNESCO, OECD and DigCompEdu, as well as reforms in the education system of Uzbekistan. The methodological foundations of using digital platforms, virtual laboratories, multimedia tools and artificial intelligence technologies for future teachers are considered. The conclusion provides scientific and practical recommendations on the integration of digital technologies in pedagogical education.